MODEL PENDEKATAN DEMOKRATIS DALAM PENGELOLAAN KELAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM SDN PLAWAD 4 KARAWANG TIMUR - kholilurahman, Muhammad fadil; Abdurrohim, Abdurrohim; mustofa, Taufik; pengelola, pengelola (STAI Ihyaul Ulum Gresik, 2025)
This study aims to develop an effective classroom management model in the subject of Islamic Religious Education (PAI) at SDN Plawad 4 East Karawang. This model is expected to assist teachers in managing the classroom, improve the quality of learning, and facilitate the spiritual and moral development of students. The research method used is qualitative by involving PAI teachers at SDN Plawad 4 East Karawang. Data collected through interviews. The results showed that the classroom management model developed succeeded in increasing active student participation, creating a conducive learning environment, and increasing students' understanding of PAI material. In addition, this model also encourages the development of mutual respect, cooperation, and social care among students. Thus, this classroom management model can be used as a reference for PAI teachers in other schools in increasing the effectiveness of PAI learning.